Review—Electrochemical Biosensors Based on ZnO Nanostructures. (1st January 2017) - Izyumskaya, N.; Tahira, A.; Ibupoto, Z. H.; Lewinski, N.; Avrutin, V.; Özgür, Ü.; Topsakal, E.; Willander, M.; Morkoç, H.
Abstract : In recent years, electrochemical biosensors based on semiconductor and metal nanostructures have attracted a great deal of attention as new instruments in the healthcare arsenal that could substantially enhance early diagnostics capabilities and thus enable active health management. Among numerous materials studied, nanostructured ZnO has been recognized as a promising platform for biomedical applications owing to its low cost, relative ease of preparation leading to a rich variety of nanostructures with high aspect ratios (nanowires, nanobelts, nanoflakes), proven biocompatibility in the bulk form, electronic properties supporting various device types, and catalytic surface activity. In this contribution, we review the recent progress in development of enzymatic and non-enzymatic biosensors based on ZnO nanostructures. After a critical discussion of biocompatibility of nanostructured ZnO, we segue into the discussion of ZnO-based devices for detection of physiologically important analytes, including glucose, cholesterol, L-lactic acid, uric acid, metal ions, and pH. Special attention is given to ZnO nanorod based sensors for intracellular measurements.